If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 88 + -32 = 6(h + -7) Combine like terms: 88 + -32 = 56 56 = 6(h + -7) Reorder the terms: 56 = 6(-7 + h) 56 = (-7 * 6 + h * 6) 56 = (-42 + 6h) Solving 56 = -42 + 6h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-6h' to each side of the equation. 56 + -6h = -42 + 6h + -6h Combine like terms: 6h + -6h = 0 56 + -6h = -42 + 0 56 + -6h = -42 Add '-56' to each side of the equation. 56 + -56 + -6h = -42 + -56 Combine like terms: 56 + -56 = 0 0 + -6h = -42 + -56 -6h = -42 + -56 Combine like terms: -42 + -56 = -98 -6h = -98 Divide each side by '-6'. h = 16.33333333 Simplifying h = 16.33333333
| 2d+36=3d-54 | | -76-9x=7x+20 | | -5n+3+4(2n+3)=41 | | 113-5x=13x+19 | | p-32=6(20-7) | | 3m+n-9m+3n= | | p-32=6(18-7) | | 120-5x=2x+15 | | -40=-5p | | 14-10x=23-17x | | 16x-278=6x-8 | | 2(x-1)=10 | | -47-3x=13-9x | | -5+17=6b-1-5b | | -8=p-13 | | 8+5(d-1)-6(d-3)=3(4-d) | | 5x-2(0)=10 | | -13+8= | | 16-(p+2)=3(p-7)+10 | | 4(0)-5y=60 | | 7x=30+40 | | 20+8(3c-2)=(c-1)+3(2c-4) | | 4x+8=57-3x | | -114-9x=10x+19 | | 4x-5y=60 | | Y=-x^2+5x+11 | | 117-3x=15x+21 | | 5x+8=107-6x | | -4x=19+9 | | 5(2x+3)=6(x+2)-2(x-4) | | Y=x^2+5x+11 | | 0=2(b-2)-3(3b+1) |